Cost‐effectiveness of botulinum neurotoxin A versus surgery for drooling: a randomized clinical trial - Bekkers, Stijn (Dev Med Child Neurol, 2020)
AIM: This study compared the cost‐effectiveness of botulinum neurotoxin A (BoNT‐A) injections with two‐duct ligation of the submandibular glands as treatment for severe drooling after one treatment cycle. METHOD: The study was part of a larger, partly single‐blinded, randomized clinical trial (trialregister.nl identifier NTR3537). Data were collected between 2012 and 2017. Evaluation was at 32 weeks after one treatment cycle. Fifty‐seven patients with cerebral palsy or other neurological, non‐progressive disorders and severe drooling classified as having a drooling frequency ≥3 or a drooling severity ≥2, in whom conservative treatment was deemed ineffective, were randomized to treatment by BoNT‐A or two‐duct ligation. An incremental cost‐effectiveness ratio (ICER) was calculated using the success rates as the measure of benefit. Treatment success was defined as a decrease ≥50% from baseline to 32 weeks in the subjective visual analogue scale for the severity of drooling or the objective drooling quotient. RESULTS: Fifty‐three patients were analysed (22 females, 31 males; mean age 11y, range 8–22y). Average costs for one treatment cycle, which included one BoNT‐A injection, were €1929 (standard error 62) for BoNT‐A and €3155 (standard error 99) for two‐duct ligation. Treatment success was in favour of two‐duct ligation (63% vs 27%; number needed to treat 3). The ICER was €34 per 1% gain in treatment success in favour of two‐duct ligation versus BoNT‐A. INTERPRETATION: The additional cost of two‐duct ligation is to some extent offset by a larger treatment success rate compared with BoNT‐A. WHAT THIS PAPER ADDS: Botulinum neurotoxin A (BoNT‐A) is less expensive per percentage of success than two‐duct ligation. The additional cost of two‐duct ligation over BoNT‐A is offset by greater treatment success.